Pengukuran Efektivitas Endorsement Melalui Akun Kreator dan Akun Publik Instagram Menggunakan TEARS Model: Studi Pada Konsumen Gen Z - Pratiwi, Anggun; Oktavia Adiwijaya, Nelly; A’yuni Ar Ruhimat , Qurrota (JURNAL SOSIAL Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
Among the many options of endorsers on public accounts as well as creator accounts on the Instagram platform, industry players must be careful in choosing the appropriate endorser who can represent the promoted product. The aim of this study is to compare the effectiveness of endorsement on creator accounts and public accounts as endorsers using the TEARS Model. This model consists of trust, expertise, attractiveness, respect, and similarity between creator account endorsers and public account endorsers. This study evaluates respondents' perceptions of two different types of endorsers based on similar advertising products, namely culinary products. This study uses descriptive analysis methods with a quantitative approach. The population used is Generation Z individuals who are Instagram social media users with a sample of 385 respondents. The results of this study show that creator account endorsers are more effective than public account endorsers. Creator accounts have a higher level of effectiveness in the dimensions of trust, attractiveness, and respect. In contrast, the dimensions of expertise and similarity with the target audience are higher in public account endorsers. Generation Z evaluates that both types of accounts have their respective advantages, where endorsement on creator accounts is more attention-grabbing and convincing, while endorsement on public accounts is more relatable due to the similarity of hobbies between endorsers and Generation Z consumers.